Cleavage of host cytokeratin-6 by lysine-specificgingipain induces gingival inflammation in periodontitis patients - Salunya Tancharoen (2018)
© 2015 Tancharoen et al. Background/Purpose: Lysine-specific gingipain (Kgp) is a virulence factor secreted from Porphyromonas gingivalis (P. gingivalis), a major etiological bacterium of periodontal disease. Keratin intermediate filaments maintain the structural integrity of gingival epithelial cells, but are targeted by Kgp to produce a novel cytokeratin 6 fragment (K6F). We investigated the release of K6F and its induction of cytokine secretion. Methods: K6F present in the gingival crevicular fluid of periodontal disease patients and in gingipaintreated rat gingival epithelial cell culture supernatants was measured by matrix-assisted laser desorption/ionization time-of-flight mass spectrometer-based rapid quantitative peptide analysis using BLOTCHIP. K6F in gingival tissues was immunostained, and cytokeratin 6 protein was analyzed by immunofluorescence staining and flow cytometry. Activation of MAPK in gingival epithelial cells was evaluated by immunoblotting. ELISA was used to measure K6F and the cytokines release induced by K6F. Human gingival fibroblast migration was assessed using a Matrigel invasion chamber assay. Results: We identified K6F, corresponding to the C-terminus region of human cytokeratin 6 (amino acids 359-378), in the gingival crevicular fluid of periodontal disease patients and in the supernatant from gingival epithelial cells cultured with Kgp. K6F antigen was distributed from the basal to the spinous epithelial layers in gingivae from periodontal disease patients. Cytokeratin 6 on gingival epithelial cells was degraded by Kgp, but not by Arg-gingipain, P. gingivalis lipopolysaccharide or Actinobacillus actinomycetemcomitans lipopolysaccharide. K6F, but not a scrambled K6F peptide, induced human gingival fibroblast migration and secretion of interleukin (IL)-6, IL-8 and monocyte chemoattractant protein-1. These effects of K6F were mediated by activation of p38 MAPK and Jun N-terminal kinase, but not p42/44 MAPK or p-Akt. Conclusion: Kgp degrades gingival epithelial cell cytokeratin 6 to K6F that, on release, induces invasion and cytokine secretion by human gingival fibroblasts. Thus, Kgp may contribute to the development of periodontal disease.